Understanding sexual prejudice among midwestern pre-service and in-service teachers: some quantitative results - Foy, Joelyn K. (My University, 2014)
Sexual orientation is only one facet of diversity (Banks et al., 2005), but teacher preparation may not adequately address sexual prejudice (Lamb, 2013). Quantitative results from a mixed methods design will be presented. BACKGROUND AND PURPOSE: School environments reinforce heteronormativity (Dean, 2010; Foucault, 1990; Himmelstein & Bruckner, 2011) such that when hate speech or physical violence occur against the non-hetersexual or the transgender student, teachers may not be prepared to respond appropriately. Students victimized because of their gender or sexual variance are more likely to skip school, resulting in lower GPAs; and are less likely to attend college (GLSEN, 2010). How do levels of sexual prejudice differ as a function of demographic, educational, and personal characteristics? METHOD: Survey results were collected from pre-service (undergraduate) and in-service teachers (graduate students). Group means of the PREJUDICE scale for each independent variable were analyzed for statistical significance. RESULTS/FINDINGS: The total variance of the PREJUDICE scale was accounted for by personal characteristics only (political, 30%; religious, 20%; non-heterosexual friends, 16%; and family members, 12%; participant sexual orientation, 8%; and finishing the survey, 4%). Neither demographic nor educational characteristics accounted for statistically significant differences in group means of the PREJUDICE scale. CONCLUSION: We do not accept or reject teacher education candidates based upon their sexual orientation or how many friends and family members they have who are non-heterosexual. Significantly lower levels of sexual prejudice were associated with having non-heterosexual friends and family members or being non-heterosexual, and there were no significant effects from educational interventions.
Keywords: Sexual orientation; Sexual prejudice; Teacher preparation; Pre-service teachers; In-service teachers